Clinicopathological characteristics and genomic profile of primary sinonasal tract diffuse large B cell lymphoma (DLBCL) reveals gain at 1q31 and RGS1 encoding protein; high RGS1 immunohistochemical expression associates with poor overall survival in DLBCL not otherwise specified (NOS). Issue 4 (9th January 2017) - Carreras, Joaquim; Kikuti, Yara Y; Beà, Sílvia; Miyaoka, Masashi; Hiraiwa, Shinichiro; Ikoma, Haruka; Nagao, Ryoko; Tomita, Sakura; Martin‐Garcia, David; Salaverria, Itziar; Sato, Ai; Ichiki, Akifumi; et al.
Abstract : Aims: We aimed to define the clinicopathological characteristics of 29 primary sinonasal diffuse large B cell lymphoma (DLBCL sn ) in a series of 240 cases of DLBCL not otherwise specified [DLBCL all ( NOS ) ], including DLBCL sn training set ( n = 11) and validation set ( n = 18), and DLBCL non‐sn ( n = 211). Methods and results: In the training set, 82% had a non‐germinal center B‐cell‐like (Hans' Classifier) (non‐GCB) phenotype and 18% were Epstein–Barr virus‐encoded small RNAs (EBER) + . The genomic profile showed gains (+) of 1q21.3q31.2 (55%), 10q24.1 (46%), 11q14.1 (46%) and 18q12.1q23 (46%); losses (−) of 6q26q27 (55%) and 9p21.3 (64%); and copy number neutral loss of heterozygosity (LOH) (acquired uniparental disomy, UPD) at 6p25.3p21.31 (36%). This profile is comparable to DLBCL NOS (GSE11318, n = 203.) and closer to non‐GCB/activated B‐cell‐like subtype (ABC). Nevertheless, +1q31, −9p21.3 and −10q11.1q26.2 were more characteristic of DLBCL sn ( P < 0.001). Array results were verified successfully by fluorescence in situ hybridization (FISH) on +1q21.3 ( CKS1B), −6q26 ( PARK2 ), +8q24.21 ( MYC ), −9p21.3 ( MTAP, CDKN2A/B ), −17p13.1 ( TP53 ) and +18q21.33 ( BCL2 ) with 82–91% agreement. Minimal common regions included biologically relevant genes of MNDA (+1q23.1), RGS1 and RGS13 (+1q31.2), FOXP1 (+3p13), PRDM1 (BLIMP1) and PARK2 (−6q21q26), MYC ( + 8q24.21), CDKN2A (−9p21.3), PTEN (−10q23.31), MDM2 (+12q15), TP53 (−17p13.1) and BCL2 (+18q21.33). Correlation between DNA copy number and protein immunohistochemistry was confirmed for RGS1, RGS13, FOXP1, PARK2 and BCL2. The microenvironment had high infiltration of M2‐like tumour associated macrophages (TAMs) and CD8 + T lymphocytes that associated with higher genomic instability. The DLBCL sn validation set confirmed the clinicopathological characteristics, all FISH loci and immunohistochemistry (IHC) for RGS1. RGS1, one of the most frequently altered genes, was analysed by IHC in DLBCL all and high RGS1 expression associated with non‐GCB, EBER + and unfavourable overall survival (hazard ratio = 1.794; P = 0.016). Conclusions: DLBCL sn has a characteristic genomic profile. High RGS1 IHC expression associates with poor overall survival in DLBCL all ( NOS ) .